A facile approach to synthesize an oxo-functionalized graphene/polymer composite for low-voltage operating memory devices1. Issue 33 (7th September 2015) - Wang, Zhenxing; Eigler, Siegfried; Ishii, Yoshitaka; Hu, Yichen; Papp, Christian; Lytken, Ole; Steinrück, Hans-Peter; Halik, Marcus
<x xml:space="preserve">Abstract</x> Polystyrene-derivative wrapped oxo-functionalized graphene, prepared by controlled chemistry, can be used as a floating gate in memory devices operating at 3 V.